Pengaruh Terapi Kombinasi Aromaterapi Lavender Dan Terapi Musik Klasik Terhadap Tingkat Stres Pada Mahasiswa Keperawatan Reguler Di Universitas Indonesia Maju Tahun 2023 - Putri Wahyu Winarsih; Sri Mintasih; Rina Afrina (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Student comes from the word student which means someone who studies or researches, students have an average age of 19 – 21 years. Stress is a common occurrence in everyday life that cannot be avoided. Stress can be experienced by individuals from all backgrounds. In reducing stress levels there are various methods used, one of which is lavender aromatherapy combination therapy and classical music therapy. To determine the effect of lavender aromatherapy and classical music therapy combination therapy on the stress level of regular nursing students at the University of Indonesia Maju Year 2023 before and after the intervention. This study used a One-Group Pretest-Posttest Pre-Experiment design with a population of 371 students, with purpossive sampling of 20 students. The data collection technique used the Depression Anxiety Scale questionnaire (DASS 42). The results showed the age of the dominant respondents 21 years as many as 15 people (75%), the majority gender of women as many as 17 people (85%), the pre-test stress level with a mean of 21,40 and the post-test stress level with a mean of 15,70. The results of bivariate analysis with shapiro wilk pretest normality test 0.202 > 0.05 posttest 0.190 > 0.05 then the data are normally distributed and dependent t-test 0.000 < 0.05 then it can be concluded that H0 is rejected, lavender aromatherapy combination therapy and classical music therapy affect the stress level of regular nursing students at the University of Indonesia Maju. Students who experience stress can do a combination therapy application of lavender aromatherapy and classical music therapy.